SHARIA BANK CORPORATE GOVERNANCE BASED ON MAQASHID SHARIA - Syahraini, Syahraini; Siregar, Saparudin; Sugianto, Sugianto (CV. Radja Publika, 2021)
This study aims to determine the effect of Good Corporate Governance as measured by the number of sharia supervisory boards, sharia supervisory board meetings, the number of boards of directors, board of directors meetings, the number of commissioners, board of commissioners meetings on the performance of maqashid sharia. The results of this study indicate that the variable meeting the board of directors has a significant effect on the performance of maqashid sharia. While the variable number of sharia supervisory board, sharia supervisory board meeting, number of board of directors, number of board of commissioners and board of commissioners meeting on maqashid sharia performance.